Pengaruh Financial Distress dan Good Corporate Governance terhadap Manajemen Laba - Eka Sulistia Minarti; Suwarno Suwarno (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This research aims to examine the effect of financial distress and good corporate governance on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (BEI). This type of research is quantitative research. The sampling method used was a purposive sampling method based on predetermined criteria. The samples used in this research were 60 samples from companies that met the criteria. The data analysis technique used is multiple linear regression analysis and is assisted by the SPSS 22.0 statistical program. The results of this research show that the variables financial distress, institutional ownership, and audit committee have no effect on earnings management. Meanwhile, managerial ownership has a negative effect on earnings management.